ЗАХИЩЕНІ ІЗОЛЯЦІЄЮ ПРОВОДИ ДЛЯ ПОВІТРЯНИХ ЛІНІЙ ЕЛЕКТРОПЕРЕДАЧІ НА СЕРЕДНЮ НАПРУГУ: ПЕРЕВАГИ, КОМПЬЮТЕРНІ РОЗРАХУНКИ - Подольцев, О.Д.; Кучерява, І.М. (Інститут електродинаміки НАН України, Київ, 2022)
The paper presents the advantages of protected insulated wires for medium-voltage (up to 35 kV) overhead power lines compared to the lines with traditional non-insulated wires. The mathematical model is developed and the computer calculations are realized for a 20 kV protected insulated wire with a steel-aluminum core. For such design, the distributions of the magnetic field and current density in three wires of overhead power line are analyzed, their resistance is determined taking into account the nonlinear properties of the steel core within the frequency range of 50–10000 Hz. This makes it possible to compute the electrical losses in the conductors of the power lines under the transient conditions and at high harmonics in the power network. References 8, figures 4.